Recaudación y Registro de los Ingresos de la Corporación de Tripulación de la Armada - Miranda Vivas, Franshesca Isabela (2018)
Non-profit entities such as cooperatives, associations or corporations are characterized as being organizations focused on developing or execute social welfare activities or for the common benefit of all members or members who are affiliated or belong to that institution. The services and benefits provided by institutions of this nature depend clearly of the administration of the entity and of the laws and agreements under which created It is public knowledge that non-profit institutions mostly they carry out self-management activities in order to finance themselves and obtain income that they will help fulfill their administrative and operational functions. The development of this case study was elaborated in the CORPORATION CREW OF THE ARMADA a non-profit entity addressed clearly in serving and benefiting the Navy crewmen, whether these are in active or passive service. This institution is domiciled in the city of Guayaquil with an extension in Samborondon locality located in the same Province of Guayas and has subsidiaries in other parts of the country, such as: Quito, Salinas and Manta, places where they are located located their Bases. This institution was created by Mr. Commander General De Marina, by order Standing Order No. CDO-001 on July 21, 1969, subsequently the statutes of the Navy Crew Corporation were approved by the President of the Republic through Ministerial Agreement No. 1360